2021
DOI: 10.1039/d1nj00864a
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal phase change induced morphology transformation in CdS/CoFe2O4@Fe2O3hierarchical nanosphere arrays as ternary heterojunction photoanodes for solar water splitting

Abstract: Design of efficient heterojunction photoanodes with appropriate band alignment and ease of charge separation has been one of the most highly focused research areas on photoelectrodes. This work demonstrates the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 91 publications
0
9
2
Order By: Relevance
“…Whereas the FCF electrode exhibited optimal photo-conversion e ciency of 1.25% (0.701 V), which was more than 1.34 times and 1.45 times that of the FFC and FCF electrodes, respectively. The ABPE and current density at 1.0V vs. SCE of the FCF electrode are higher than those of Maitra et al [35], and this FCF photoelectrode also showed better performance in terms of the light response.…”
Section: Electrochemical Properties Of the α-Fe 2 O 3 Filmscontrasting
confidence: 60%
“…Whereas the FCF electrode exhibited optimal photo-conversion e ciency of 1.25% (0.701 V), which was more than 1.34 times and 1.45 times that of the FFC and FCF electrodes, respectively. The ABPE and current density at 1.0V vs. SCE of the FCF electrode are higher than those of Maitra et al [35], and this FCF photoelectrode also showed better performance in terms of the light response.…”
Section: Electrochemical Properties Of the α-Fe 2 O 3 Filmscontrasting
confidence: 60%
“…Fe 2p core-level spectra is shown in Figure b. The peaks at 710.2 and 724.6 eV correspond to Fe 3+ 2p 3/2 and Fe 3+ 2p confirming the presence of Fe in its 3+ state present at the O h sites. ,,, Alongside this, peaks at 713.3 and 726.4 eV correspond to the presence of Fe 3+ 2p 3/2 and Fe 3+ 2p, confirming the presence of Fe in its 3+ state present at the tetrahedral sites, thereby showing that successful spinel inversion has occurred, because Fe is present in both octahedral and tetrahedral sites. ,,,,, The δ parameter can be calculated from the area ratio of the octahedral and tetrahedral site peaks of Fe 2p and Cu 2p, according to Fantauzzi et al The ratio of Fe:Cu in the analyzed sample CuFeM was observed to be 1.9. The general formula for CuFe 2 O 4 spinel is [Fe δ Cu 1−δ ]­( T d )­[Cu δ Fe 2−δ ]­(O h )­O 4 .…”
Section: Resultsmentioning
confidence: 74%
“…The probable mechanism for the porosity enhancement is as follows. Alcoholic solution in the solvothermal process inhibits mineralization into hydroxides and oxyhydroxides, which, after annealing, can potentially lead to formation of impure oxides, thereby causing a direct change into copper ferrite from parent hematite without impurities as observed from our previous work A precursor solution containing a high concentration of Cu ions capped with surfactants in the absence of mineralizers are energetically deterred from forming clusters among themselves, but at the hematite/solution interface at high temperature in the autoclave, impregnation of these ligand-capped ions into the hematite lattice occurs, causing a direct phase change to copper ferrite. The impregnation of these ligand-capped ions into the hematite lattice under high pressure and temperature causes a change in morphology, resulting in enhanced porosity in the fabricated nanostructures.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, room‐temperature PL spectra were measured to characterize the recombination rate of photocharge carriers. [ 29–31 ] From Figure 2d, peaks due to the band‐edge emission are observed around 595 nm (2.08 eV). The characteristic emission peaks of 50‐faceted Cu 2 O are much lower than others, indicating that the recombination of photocharge carriers could be effectively restrained, thus resulting in an enhanced photocatalytic activity for 50‐faceted Cu 2 O.…”
Section: Resultsmentioning
confidence: 99%